Contextual Theological Analysis of Mayo Boyo Practice among the Maybrat Tribe in Jayapura City - Yosep Kambu (Institut Kristen Teologi Real Batam, 2026)
This study examines the tension between the Mayo Boyo (dowry) tradition of the Maybrat community in Jayapura City and Christian theological perspectives, particularly in relation to justice, human dignity, and the sacredness of marriage. It investigates how Mayo Boyo can be interpreted within a Christian theological framework without disregarding its cultural significance. Using a qualitative grounded theory design, the study employs hermeneutic analysis to examine Mayo Boyo as a socio-cultural practice in light of the Gospel. The findings indicate that Mayo Boyo functions as an important relational and symbolic institution that strengthens family and communal ties. However, it may also shift toward economic burden and the commodification of marriage when practiced without critical reflection. The study argues for a pastoral contextual theological approach that reinterprets Mayo Boyo through dialogue with Christian teachings while preserving its constructive cultural values. Such an approach enables cultural continuity while affirming the Christian principles of love, justice, and human dignity. Abstrak Penelitian ini mengkaji ketegangan antara tradisi Mayo Boyo (mas kawin) dalam masyarakat Maybrat di Kota Jayapura dan perspektif teologi Kristen, khususnya yang berkaitan dengan keadilan, martabat manusia, dan kesakralan perkawinan. Penelitian ini bertujuan untuk memahami bagaimana praktik Mayo Boyo dapat dimaknai dalam kerangka teologi Kristen tanpa mengabaikan nilai-nilai budaya yang melekat di dalamnya. Penelitian menggunakan pendekatan kualitatif dengan desain grounded theory serta analisis hermeneutik terhadap Mayo Boyo sebagai praktik sosial-budaya dalam terang Injil. Hasil penelitian menunjukkan bahwa Mayo Boyo memiliki fungsi relasional dan simbolik yang penting dalam memperkuat ikatan keluarga dan komunitas. Namun, praktik ini juga berpotensi bergeser menjadi beban ekonomi dan bentuk komodifikasi perkawinan apabila dijalankan tanpa refleksi yang kritis. Oleh karena itu, penelitian ini mengusulkan pendekatan teologi kontekstual pastoral yang menafsirkan kembali Mayo Boyo melalui dialog dengan ajaran Kristen, sekaligus mempertahankan nilai-nilai budaya yang bersifat konstruktif. Pendekatan tersebut memungkinkan tradisi budaya tetap lestari sejalan dengan prinsip kasih, keadilan, dan martabat manusia dalam iman Kristen.